6x-1=6(x+9)

Simple and best practice solution for 6x-1=6(x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-1=6(x+9) equation:


Simplifying
6x + -1 = 6(x + 9)

Reorder the terms:
-1 + 6x = 6(x + 9)

Reorder the terms:
-1 + 6x = 6(9 + x)
-1 + 6x = (9 * 6 + x * 6)
-1 + 6x = (54 + 6x)

Add '-6x' to each side of the equation.
-1 + 6x + -6x = 54 + 6x + -6x

Combine like terms: 6x + -6x = 0
-1 + 0 = 54 + 6x + -6x
-1 = 54 + 6x + -6x

Combine like terms: 6x + -6x = 0
-1 = 54 + 0
-1 = 54

Solving
-1 = 54

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 40x+15(1.5x)=676 | | 6=2(u+6)-8u | | x+x=what | | L+2=6l-48 | | 15x+5+11x-7=180 | | -x(x+y)=-2 | | 11r-60=16 | | 9z+1=10z-3 | | 6y+22=4y | | 33x×33x×33x÷3x×3x/11 | | 21x+5+8x+1=180 | | 6(-6)+x=76-2x | | 1x+5+8x+1=180 | | 9-7=x/4 | | 6x-19+3x+7+87=180 | | 6(-6)+x=76-2 | | y=5/5-2x | | 23y-14y=-512y+12 | | 121=11x+22 | | 1/3cosX/4=1/9 | | 6(3x+6)=-108 | | 3x^2-2xy-9=0 | | 21x^10/3x^5 | | 2xy+2yx=6 | | 13x^2-2x+453=0 | | 1/7x5/2 | | 3x+7x=16+6x | | 12c+6=-15 | | 1+3m-5m=5 | | y=4=1/2(x-3) | | 3v-11=31 | | 30=-5n[6n+6] |

Equations solver categories